Improving musculoskeletal health for children and young people – A 'call to action'. Issue 5 (October 2020) - Foster, Helen E.; Scott, Christiaan; Tiderius, Carl J.; Dobbs, Matthew B.; ,; Ang, Elizabeth; Charuvanij, Sirirat; Costello, Wendy; Kinnunen, Marja; Lewandowski, Laura B.; Migowa, Angela; Stones, Simon R.; et al.
Abstract: This chapter describes the musculoskeletal (MSK) context in children and young people as an important contributor to the global non-communicable disease burden. Through selected MSK conditions, we describe the impact on patients, families and communities and highlight the challenges that need to be addressed. We focus on opportunities for better working together and describe exemplar initiatives to raise awareness, workforce capacity building, models of care and research agendas to have a greater global context.